Catalytic Dehydrative Transformations Mediated by Moisture-Tolerant Zirconocene Triflate - Margarita, Cristiana; Di Francesco, Davide; Lundberg, Helena (Synlett, 2023)
Zirconocene triflate is a powerful moisture-tolerant catalyst for activation of C–O bonds in carboxylic acids and alcohols in the absence of water scavenging techniques. Herein, an overview of the use of this robust metal complex for direct amidation, esterification, and etherification is presented, along with a discussion on mechanistic aspects of the transformations and the catalyst class.
Keywords: Lewis acids; homogeneous catalysis; water-tolerant; kinetic analysis; zirconium; amides; esters; ethers